Zooarchaeological database of Late Roman Implenia Mühlegasse (Kaiseraugst, Switzerland) - Grau-Sologestoa, Idoia; Deschler-Erb, Sabine (Zenodo, 2021)
The site of Implenia Mühlegasse (2008.003 DH) is located in Kaiseraugst, north-western Switzerland. Implenia Mühlegasse lies in the suburbs of the Castrum Rauracense, a fortification built in Late Roman times north of the city of Augusta Raurica, in the southern bank of the Rhine river, which was at the time the frontier of the Roman Empire in this region. This database contains the zooarchaeological information of the inventory of the faunal materials recovered at the site (mainly from middens), all hand-collected. There are approximately 1500 MNE (Minimum Number of Elements). The recorded data are: taxon, skeletal element, taphonomy (butchery marks, overal preservation, colour, etc.), and biometrical data. The majority of the remains are dated to the 4th and 5th centuries. The assemblage is predominated by cattle, followed by pig. Other identified species are: sheep/goat, equids, aurochs, red deer, wild boar, dog, cat, fox, hare, Anas sp., chicken, partridge, pigeon, Turdus sp, small Murinae, Salmo (salar?) and human. The site and its stratigraphy was thoroughly examined and published in: Flückiger, A. 2018. Kaiseraugst zwischen Spätantike und Frühmittelalter. Eine siedlungsarchäologische Studie. PhD dissertation, Universität Basel. We would like to thank Anna Flückiger, Sandra Ammann and the Museum Augusta Raurica for their collaboration.